2012
DOI: 10.1021/jp212043v
|View full text |Cite
|
Sign up to set email alerts
|

Controlling Space Charge of Oxide-Free Si by in Situ Modification of Dipolar Alkyl Monolayers

Abstract: Good passivation of Si, both electrically and chemically, is achieved by monolayers of 1,9-decadiene, directly bound to an oxide-free Si surface. The terminal CC bond of the decadiene serves for further in situ reaction, without harming the surface passivation, to −OH- or −Br-terminated monolayers that have different dipole moments. Such a two-step procedure meets the conflicting requirements of binding mutually repelling dipolar groups to a surface, while chemically blocking all surface reactive sites. We de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
62
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 22 publications
(63 citation statements)
references
References 45 publications
1
62
0
Order By: Relevance
“…[ 38 ] A back contact to the Si was made with an InGa-eutectic. [ 18,47 ] Current-voltage measurements were performed with a Keithley 6430 sub femtoamp source-meter, within a vacuum probe station (LakeShore), equipped with LHe cooling and temperature controller (LakeShore, 336). Current-voltage scans were measured from 0 V to −1 V, to +1 V and back to 0 V in 10 mV steps.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…[ 38 ] A back contact to the Si was made with an InGa-eutectic. [ 18,47 ] Current-voltage measurements were performed with a Keithley 6430 sub femtoamp source-meter, within a vacuum probe station (LakeShore), equipped with LHe cooling and temperature controller (LakeShore, 336). Current-voltage scans were measured from 0 V to −1 V, to +1 V and back to 0 V in 10 mV steps.…”
Section: Methodsmentioning
confidence: 99%
“…[ 46 ] However, transport across the SCR is also very sensitive to interface traps. Therefore, while the molecular electrostatic effect can tolerate inhomogeneities in the monolayer, the underlying Si substrate should have a low enough density of residual oxides [ 22,47 ] or dangling bonds, [ 41 ] so that their effects do not dominate the transport. For oxides, we found that even 1% atomic or less can dominate transport.…”
Section: Moderately Doped Si: Combined Molecular and Si Barriersmentioning
confidence: 99%
“…32 Note that incorporation of device inhomogeneity is crucial for an accurate modeling of J-V characteristics, otherwise artificially large interface defect densities may be required to account for the large values of the apparent ideality factor. 80 The lateral spatial extension of the low barrier height regions can be estimated from the distribution of c values, derived in the framework of the patch model, which considers that the smaller low barrier height patches are "pinched off." In the limited range of c values, 8-18 Â 10 À4 cm 2/3 V 1/3 , used to describe experimental transport data, the corresponding typical patch radius R P values are expected between 0.2 and 0.5 lm (setting arbitrarily D P % 0.3 eV), which is consistent with the requirements of the dipole approximation, i.e., R P is smaller than the width of the space charge layer W ¼ ð2V bb gÞ 1=2 , with g ¼ ðe S =qN D Þ ¼ 4.4 Â 10 À8 cm 2 V À1 , as long as the band bending V bb ¼ U B À V À V n is larger than 30 mV.…”
Section: Distribution Of Interface Barrier Heightsmentioning
confidence: 99%
“…In this regard, the use of fluorinated alkynes would provide an easily accessible additional tool, namely the stepwise variation of the work function of the underlying Si NWs surface. [32][33][34] In this study, we investigated the formation of five different 1-hexadecyne-derived monolayers with a varying number of fluorine atoms (HCC-(CH 2 ) 6 C 8 H 17-x F x ; x = 0, 1, 3, 9, 17) onto oxidefree hydrogen-terminated Si NWs by a one-step hydrosilylation using 1-alkynes F0 to F17 (Scheme 1). These monolayers were characterized in detail by X-ray photoelectron spectroscopy (XPS), infrared spectroscopy (IR), static contact angle measurements, scanning electron microscopy (SEM) and transmission electron microscopy (TEM …”
Section: Introductionmentioning
confidence: 99%